Pengaruh Total Aset Turnover (TATO), Earning Per Share (EPS), Debt To Assets Ratio (DAR) Terhadap Harga Saham Pada Industri Farmasi - Desy Istiyowati; Ika Swasti Putri (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this study is to analyze the effect of Total Assets Turnover (TATO), Earning Per Share (EPS), Debt To Assets Ratio (DAR) on Stock Prices in Pharmaceutical Industry companies listed on the Indonesia Stock Exchange (IDX). The period used in this study is 5 (five) years, starting from 2016-2020. This study uses a quantitative approach. The sampling technique used was purposive sampling and obtained a sample of 9 (nine) companies. The data analysis technique used is multiple linear regression. The results showed that partially Total Assets Turnover (TATO) had a positive and significant effect on stock prices, indicated by a significant value of 0.418. The Earning Per Share (EPS) variable has a negative and significant effect on stock prices, indicated by a significant value of 0.329. The variable Debt To Assets Ratio (DAR) has a negative and insignificant effect on stock prices, indicated by a significant value of 0.007. The ability of the variable Total Assets Turnover (TATO), Earning Per Share (EPS), Debt To Assets Ratio (DAR) in explaining the dependent variable Share Price is 13.7% as indicated by the adjusted R square of 0.137% while the remaining 86.3% influenced by other factors not included in the research model.